ESR statement on new approaches to undergraduate teaching in Radiology (Insights Imaging, 2019)
Medical education is evolving and electronic learning (e-Learning) strategies have now become an essential asset in radiology education. Radiology education is a significant part of the undergraduate medical curriculum and the use of e-Learning in radiology teaching in medical schools is on the rise. If coupled with clinical decision support systems, e-Learning can be a practical way of teaching students clinical decision making, such as selecting the diagnostic imaging tests that are best suited in certain clinical scenarios. The innovative concept of flipped classroom learning encourages students to work independently and maximises the application of learnt contents in interactive classroom sessions. For integrated curricula with their student-centred, problem-based, and community-based design, an approach to systematically integrate radiology may be to define diagnostic reasoning as one of the core goals. Radiologists as teachers and scholars may understand themselves as experts in diagnostic reasoning and in mentoring how to make medical decisions. Computer programs simulating the routine work are available and can be used to teach the recognition of anatomical structures and pathological patterns, and also to teach ultrasonography and interventional radiology, maximising patient safety.